ANALISIS ETOS KERJA DALAM PENINGKATAN KINERJA PEGAWAI NEGERI SIPIL PADA BAGIAN UMUM SEKRETARIAT DAERAH KABUPATEN NIAS SELATAN - HIA, YUSNI HARTATI; PANJAITAN, FERRY; MANALU, DIMPOS (LP2MTBM MAKARIOZ, 2023)
Public demands to continue to improve the performance of civil servants in the general section of the South Nias Regency Regional Secretariat are increasing which has an impact on the Employee Work Ethic. This study aims to describe and analyze the work ethic in improving the performance of civil servants in the General Section of the Regional Secretariat of South Nias Regency. This research uses a descriptive qualitative research method. In this case all the elements in this study are directed to provide information on questions through interviews. Based on the results of the study, the analysis of work ethic in improving the performance of civil servants in the general section of the South Nias Regency Regional Secretariat which was studied from several dimensions such as tenacity, obedience, quality of work, and responsiveness was still not optimal or low, and was supported by the results of interviews with research informants. affect performance levels. The policy recommendation given is that the heads of the work units of the South Nias Regency Regional Secretariat should improve the performance of civil servants by giving awards or rewards, namely by giving employees the opportunity to attend training.